Lung involvement by chest CT images in covid-19 patients in a Specialty Hospital in the Northeast of Mexico - Garcia Alvarado, Francisco Javier; Muñoz Hernández, Melisa Alejandra; Segura Lopez, Fany Karina; Delgado-Aguirre, Héctor Alberto; Gaona Hernández, Yazmín Esmeralda; Arellano Rosales, Jaime Suriel (Acta Universitaria, 2022)
Chest imaging (CT) plays an important role in the detection and diagnosis of covid-19. The objective of this study is the local experience of CT-based semi-quantitative score of lung involvement as well as the clinical staging in covid-19 patients at the Specialty Medical Institution No. 71 (UMAE, from its Spanish acronym). This is a single- center, retrospective study, in which 71 patients (44 men, 27 women; mean age 50 ± 14.1, range 25-84 years) were selected with positive tests of RT-PCR for SARS-CoV-2 and a confirmed diagnosis of covid-19. Chest CT images showed as predominant pattern the mixed pattern (n = 26, 36.6%), and other common findings included ground glass opacities (GGO) (n = 25, 35.2%), crazy paving (n = 15, 21.1%), and lung consolidation (n = 5, 7.0%). The chest computed tomography findings were bilateral lesions (n = 64, 90.1%), subpleural distribution (n = 61, 85.9%), and lower lobes (n = 31, 43,6%). The characteristic pulmonary tomographic pattern was ground-glass opacities and a bilateral mixed pattern of peripheral distribution towards the posterior regions.